Estimation of the Earth’s tensor of inertia from recent geodetic and astronomical data - Marchenko, A.N.; Yarema, N.P. (Геодинаміка, 2009)
The transformation of the second-degree harmonic coefficients C2m and S2m in the case of a finite commutative rotation was derived instead of the traditional Lambeck’s approach based on an infinitesimal rotation.